How microorganisms use hydrophobicity and what does this mean for human needs? - Krasowska, Anna; Sigler, Karel (Frontiers in Cellular and Infection Microbiology, 2014)
Cell surface hydrophobicity (CSH) plays a crucial role in the attachment to, or detachment from the surfaces. The influence of CSH on adhesion of microorganisms to biotic and abiotic surfaces in medicine as well as in bioremediation and fermentation industry has both negative and positive aspects. Hydrophobic microorganisms cause the damage of surfaces by biofilm formation; on the other hand, they can readily accumulate on organic pollutants and decompose them. Hydrophilic microorganisms also play a considerable role in removing organic wastes from the environment because of their high resistance to hydrophobic chemicals. Despite the many studies on the environmental and metabolic factors affecting CSH, the knowledge of this subject is still scanty and is in most cases limited to observing the impact of hydrophobicity on adhesion, aggregation or flocculation. The future of research seems to lie in finding a way to managing the microbial adhesion process, perhaps by steering cell hydrophobicity.